(untitled) - Evening, Martin (Amsterdam, 2004)
'This publication is a must for all photographers, independent of your level of experience with the package, as it's written by a practising professional photographer with you, the photographer, in mind
Keywords: Computer graphics,Photography,Đồ hoạ vi tính,Chụp ảnh; Digital techniques,Kỹ thuật số